122k views
5 votes
-10\left(-\frac{1}{2}+\left(-\frac{7}{2}\right)+7y=25

1 Answer

0 votes

Answer:


y=(47)/(14)

Explanation:

Given


-10\left(-(1)/(2)\right)+\left(-(7)/(2)\right)+7y=25

Required

Solve for y


-10\left(-(1)/(2)\right)+\left(-(7)/(2)\right)+7y=25

Open brackets


(10)/(2)-(7)/(2)+7y=25

Collect Like Terms


7y=25 -(10)/(2)+(7)/(2)

Take L.C.M


7y=(50-10+7)/(2)


7y=(47)/(2)

Divide both sides by 7


y=(47)/(2*7)


y=(47)/(14)

User Beibei
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.